What it Takes To Be an Effective Lecturer: A Case Study in Universiti Putra Malaysia - Rajan, Sundari (1999)
The purpose of this qualitative case study was to understand what it takes to be an effective lecturer for graduate students in Universiti Putra Malaysia. This was done by examining three research objectives which is 1) to understand who is an effective lecturer, 2) to understand hoe concept of learning and teaching influences the effectiveness of the lecturer and 3) to find out the factors affecting the effectiveness of the lecturers. Five lecturers were selected from a list of lecturers who won the award of excellence for the year 1997. All five lecturers were from different faculty and area of specialization. The awards of excellence lecturers are evaluated by the University by using a systematic and standardized form, which focuses on researches, teaching and community services. The lecturers were selected using purposive sampling and data was obtained from interview, other documents and e-mail correspondence. Findings revealed that an effective lecturer should 1) possess positive personality, have certain qualification , experience, training, skills and be knowledgeable 2) understand the concepts of learning and teaching and how it influences the effectiveness and finally 3) identify the factors that affects the effectiveness of the lecturer.